2012
DOI: 10.1002/elan.201200104
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Graphene Nanosheets for Miniaturization of Potentiometric Urea Lipid Film Based Biosensors

Abstract: The present article describes a miniaturized potentiometric urea lipid film based biosensor on graphene nanosheets. Structural characterization of graphene nanosheets for miniaturization of potentiometric urea lipid film based biosensors have been studied through atomic force microscopy (AFM) and transmission electron microscopy (TEM) measurements. UV‐Vis and Fourrier transform IR (FTIR) spectroscopy have been utilized to study the pre‐ and postconjugated surfaces of graphene nanosheets. The presented potentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 42 publications
0
41
0
6
Order By: Relevance
“…Graphene nanosheets have been successfully exfoliated onto a thin copper wire and exploited for the miniaturization of a potentiometric urea biosensor [29]. A miniaturized potentiometric urea lipid film-based biosensor on graphene nanosheets was developed.…”
Section: Examples Of Biosensors Based On Lipid Modified Graphene Micrmentioning
confidence: 99%
“…Graphene nanosheets have been successfully exfoliated onto a thin copper wire and exploited for the miniaturization of a potentiometric urea biosensor [29]. A miniaturized potentiometric urea lipid film-based biosensor on graphene nanosheets was developed.…”
Section: Examples Of Biosensors Based On Lipid Modified Graphene Micrmentioning
confidence: 99%
“…Later on, lipid polymer membranes supported on glass fiber were shown to be stable in air [5]. The deposition of these polymer lipid films on graphene electrode [3] offered many advantages such as increased sensitivity and selectivity, rapid response times, and provided remote sensing biosensors for urea.…”
Section: Polymer Lipid Membranesmentioning
confidence: 99%
“…The results of Raman and IR showed that the polymerization kinetics ended after four hours. The polymerization mechanism and generation of the signal was further on explored by Raman and IR spectroscopy, micro-Raman spectroscopy, DSC, and SEM experiments [2,3,9,10]. These membranes were stable for storage in air for a period of longer than two months.…”
Section: Polymer Lipid Membranesmentioning
confidence: 99%
See 2 more Smart Citations